Joseph Pulitzer papers - Pulitzer, Joseph, 1885-1955.
Family and general correspondence, subject files, business files, and personal financial records relating primarily to Pulitzer's editorship of the St. Louis Post-Dispatch. Documents the operation and production of the newspaper including its working philosophy, internal business management, and editorial policies. Includes extensive files of correspondence between Pulitzer and his editorial and reporting staffs and other journalists, as well as his correspondence with local St. Louis and national government officials. Subjects include national and international affairs, Franklin D. Roosevelt's court-packing plan in 1937, World War II, an inspection of Nazi concentration camps, business trends, fraudulent advertising, and the American Newspaper Guild. Includes material pertaining to Pulitzer's personal and family life, Joseph Pulitzer, Sr., the Pulitzer estate, administration of the Pulitzer Prize, and Pulitzer's interest in fishing and hunting.
Correspondents include Paul Y. Anderson, Bernard M. Baruch, Oliver Kirby Bovard, Raymond P. Brandt, Richard Evelyn Byrd, Norman Chandler, Marquis W. Childs, James Bryant Conant, Raymond L. Crowley, Dwight Filley Davis, Frederick Trubee Davison, Irving Dilliard, Cyrus Stephen Eaton, Ernest Gruening, Jesse H. Jones, David Lawrence, Walter Lippmann, Agnes Elizabeth Ernst Meyer, Eugene Meyer, Ogden Livingston Mills, Charles Nagel, Adolph S. Ochs, Joseph Medill Patterson, Benjamin Harrison Reese, Charles G. Ross, Franklin D. Roosevelt, Wesley Winans Stout, Arthur Hays Sulzberger, Herbert Bayard Swope, Stuart Symington, Norman Thomas, Arthur H. Vandenberg, Oswald Garrison Villard, Sumner Welles, and John N. Wheeler.
Microfilm edition available
Microfilm edition produced from originals in the Manuscript Division.
Newspaper editor and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Paul Y., -- 1893-1938 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Bovard, Oliver Kirby, -- 1872-1945 -- Correspondence; Brandt, Raymond P. -- 1896-1974 -- Correspondence; Byrd, Richard Evelyn, -- 1888-1957 -- Correspondence; Chandler, Norman, -- 1899- -- Correspondence; Childs, Marquis W. -- 1903-1990 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; Crowley, Raymond L. -- Correspondence; Davis, Dwight Filley, -- 1879-1945 -- Correspondence; Davison, Frederick Trubee, -- 1896- -- Correspondence; Dilliard, Irving, -- 1904-2002 -- Correspondence; Eaton, Cyrus Stephen, -- 1883-1979 -- Correspondence; Gruening, Ernest, -- 1887-1974 -- Correspondence; Jones, Jesse H. -- 1874-1956 -- Correspondence; Lawrence, David, -- 1888-1973 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Meyer, Agnes Elizabeth Ernst, -- 1887-1970 -- Correspondence; Meyer, Eugene, -- 1875-1959 -- Correspondence; Mills, Ogden Livingston, -- 1884- -- Correspondence; Nagel, Charles, -- 1849-1940 -- Correspondence; Ochs, Adolph S. -- 1858-1935 -- Correspondence; Patterson, Joseph Medill, -- 1879-1946 -- Correspondence; Pulitzer, Joseph, -- 1847-1911.; Reese, Benjamin Harrison, -- 1888- -- Correspondence; Ross, Charles G. -- 1885-1950 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Stout, Wesley Winans, -- 1890- -- Correspondence; Sulzberger, Arthur Hays, -- 1891-1968 -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; Symington, Stuart, -- 1901-1988 -- Correspondence; Thomas, Norman, -- 1884-1968 -- Correspondence; Vandenberg, Arthur H. -- 1884-1951 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Welles, Sumner, -- 1892-1961 -- Correspondence; Wheeler, John N. -- 1886- -- Correspondence; Pulitzer family; Pulitzer family -- Correspondence; United States. -- Supreme Court; St. Louis post-dispatch.; American newspapers -- Missouri; Deceptive advertising; Fishing; American Newspaper Guild; Hunting; International relations; Journalism; Judges -- Selection and appointment -- United States; Pulitzer Prizes; World War, 1939-1945.; World War, 1939-1945 -- Concentration camps; Missouri -- Politics and government; Saint Louis (Mo.) -- Politics and government; United States -- Economic conditions -- 20th century; United States -- Foreign relations -- 20th century; United States -- Politics and government -- 20th century; Newspaper editors; Publishers